A dynamic time-temperature-dependent process for thermal oxidation of Sn leading to SnOx thin films: Impedance spectroscopy study - Barreira, Enzo A. [UNESP]; Pedrini, Luiz F. K. [UNESP]; Boratto, Miguel H. [UNESP]; Scalvi, Luis V. A. [UNESP] (World Scientific Publ Co Pte Ltd, 2020)
Tin dioxide (SnO2) thin films are obtained from resistive evaporation of metallic Sn followed by thermal oxidation at different temperatures in the range 200-500 degrees C. Results show that, besides the thickness of the evaporated Sn thin film, the oxidation process of Sn into SnO2 is highly dependent on the annealing time and temperature, presenting tin monoxide (SnO), as an intermediate compound, result of partial oxidation of the metallic Sn at intermediary time and temperature. The optical and electrical properties of the Sn thin films are altered by the oxidation degree of Sn into SnOx. These important characteristics are evaluated through UV-Vis, SEM, EDS, XRD and Impedance Spectroscopy. Increase in the optical bandgap energy as well as in the surface charge density, verified by electrical impedance, are observed on samples with higher annealing temperature and time, which indicate sequential oxidation process in these films.
Keywords: Tin dioxide; resistive evaporation; oxidation; impedance spectroscopy